Methodological considerations in assessing the effectiveness of antidepressant medication continuation during pregnancy using administrative data1. (4th June 2015) - Swanson, Sonja A.; Hernandez‐Diaz, Sonia; Palmsten, Kristin; Mogun, Helen; Olfson, Mark; Huybrechts, Krista F.
Abstract Purpose The decision whether to continue antidepressant use for depression during pregnancy requires weighing maternal and child risks and benefits. Little is known about the effectiveness of antidepressant therapy during pregnancy. The goal of this study is to evaluate whether standard administrative claims data can be used to evaluate the effectiveness of antidepressants. Methods Using prescription and healthcare visit Medicaid claims (2000–2007), we identified 28 493 women with a depression diagnosis and antidepressant fill in the 90 days before their last menstrual period. Antidepressant continuation was defined based on prescription fills during the first trimester. Depression hospitalizations and deliberate self‐harm served as measures of the effectiveness of treatment continuation during pregnancy. Propensity score and instrumental variable analyses were used to attempt to account for confounding. Results Relative to women who discontinued antidepressant therapy, women who continued were more likely to have a depression inpatient stay (odds ratio [OR] = 2.2, 95% confidence interval [95%CI]: 2.0–2.4) and deliberate self‐harm code (OR = 1.4, 95%CI: 0.7–2.7). Accounting for measured covariates in the propensity score analysis, including age, race, comorbidities, comedications, features of the depression diagnosis, and antidepressant class, led to slightly attenuated estimates (OR = 2.0, 95%CI: 1.8–2.2; OR = 1.1, 95%CI: 0.5–2.4). Similar associations were estimated in subgroups with different levels of baseline depression severity. Proposed preference‐time, calendar‐time‐based, and geography‐based instruments were unlikely to meet the required conditions for a valid analysis. Conclusions Our findings suggest that either antidepressant medications do not reduce the risk of depression relapse in pregnant women, or that administrative data alone could not be used to validly estimate the effectiveness of psychotropic medications during pregnancy. Copyright © 2015 John Wiley & Sons, Ltd.